ANTIBACTERIAL EFFECTIVENESS OF VARIOUS TYPES OF HERBS EXTRACTS ON THE DIAMETER OF THE GROWTH INHIBITION ZONE OF Aeromonas salmonicida - Nashir Arifin; Maria Agustini; Sri Oetami Madyowati; Achmad Kusyairi (Jurnal Perikanan Unram, 2024)
The use of chemicals such as antibiotics, immunostimulants and vaccines is one of the efforts that can be made to prevent disease attacks on fish. However, using chemicals such as antibiotics over a long period of time with inappropriate use will make disease-causing bacteria become resistant to these materials. Therefore, it is necessary to look for herbal ingredients as a substitute for antibiotics, for example the Chinese betel plant, anting anting plant and basil plant. The aim of this research was to determine the effect of different herbal plant extracts in inhibiting the growth of Aeromonas salmonicida bacteria. The research method used was experimental with an experimental design using a completely randomized design (CRD) consisting of 3 treatments, 9 replications. The Kirby-Bauer disc diffusion method was used in this research. Chinese betel simplicia, anting earrings and basil were soxhleted with 95% ethanol solvent until the solution was colorless and concentrated using a rotary evaporator. Next, an antibacterial test was carried out. The research results showed that the highest inhibitory power for the growth of Aeromonas salmonicida bacteria was obtained in the treatment of Chinese betel extract (Peperomia pellucida L) with an average of 7.75 mm, then in the treatment of anting anting extract (Acalypha indica L) with an average of 6.61 mmm. in the basil extract treatment (Ocimum sanctum L) the lowest growth inhibition zone was obtained, namely an average of 5.67 mm. Based on the Anova test with F count (0.000) > F table at a significance level of 5%, which means it shows that herbal plant extracts in each treatment have a significant effect on the growth inhibition of Aeromonas salmonicida bacteria.